This Must Be the Place - Rodgers, Susan Jackson, 1960- (Book collections on Project MUSE., 2017)
"It's the summer of 1983. Ronald Reagan is in the White House, Princess Leia is on magazine covers, and Thea Knox is on the road. Fresh out of college, Thea is driving solo from California to New York. Her plan is to house-sit for her parents for the summer, but they sell her childhood home on a whim, leaving Thea (once again) to her own devices. She takes a detour to visit her Aunt Wendy in Merdale, a college town nestled in the Kansas prairie. Unlike Dorothy, Thea's adventure begins when she arrives in Kansas. Thea is immediately surrounded by her aunt's group of friends, including Julie, a bookstore owner; Nick, Julie's carpenter boyfriend; Bob, a stoner wildlife rehabilitator; and Amira, a lawyer who works with runaway girls. When she finds herself in love at first sight with Jimmy Ward, a local with a hazy past, Thea decides to extend her stay. Not everyone welcomes her into the fold, however, and Thea's own past--including her distant best friend and erstwhile boyfriends on either coast--is nipping at her heels. When she discovers a terrible secret that could upend Jimmy's world, the spell of happiness she has woven in this unlikely place threatens to break. This compelling coming-of-age novel explores the search for identity, love, friendship, and home, and celebrates the magic and mystery that exist in even the most ordinary places"--